Efficiency and Productivity of Indonesian Islamic Banking - Pipit Afiatun, Sudarso Kadei Wiryono (ITB, 2010)
The direction of the Indonesia banking industry development policy based on the vision of achieving a healthy banking system, strong and efficient to create a stable financial system in order to driver national economic growth. Using Analysis of efficeiency and changes in Total factor Productivity of the banking industry during the 2004 to 2009 period, this research aims to observe at the performance of islamic banking as the new actors of Indonesian banking industry. To analyze the effciency, this research utilize the method of non parametric Data Envelopment Analysis (DEA). To Measure changes in Total Factor productivity of Islamic banking industry Mamquist Productivity Index is utilized. From the calculation of relative efficiency by means of input-oreiented DEA and also the assumption of Variable Returns to scale, the study indicated that the efficeiency of Islamic anks in the 2004-2009 period are lower on the average compared to conventional banks; exept during the period of july 2004 to December 2005. There are three Islamic banks analyzed for this particular research, namely Bank Muamalat, Bank Syariah Mandiri, and Bank Syariagh Mega, consectively ranked 3rd, 10th, and 13th within the index of productivity. Yet, the results of t-test concluded that the efficency and productivity of Islamic banks and conventional banks, statistically, are not significantly different,. Theseresults indicated that Islamic bankingin general prossess the ability to compete with conventional banking in Indonesia.